Deletion of Neuropeptide Y Attenuates Cardiac Dysfunction and Apoptosis During Acute Myocardial Infarction - Huang, Wei; Zhang, Qianhui; Qi, Hanping; Shi, Pilong; Song, Chao; Liu, Yongsheng; Sun, Hongli (Frontiers in Pharmacology, 2019)
Increasing neuropeptide Y (NPY) has been shown to be a risk factor for cardiovascular diseases. However, its role and mechanism in myocardial infarction (MI) have not yet been fully understood. H9c2 cells and neonatal rat ventricular myocytes (NRVMs) with loss of function of NPY and rats with global knockout were used in this study. Myocardial infarction model of rats were induced by the ligation of left coronary artery and the extent of MI was analyzed through echocardiographic, pathological, and molecular analyses. Our data demonstrated that NPY expression was significantly increased in MI rats and hypoxia/H2O2-treated cardiomyocytes. At the same time, NPY-knockout (NPY-KO) rats exhibited a remarkable decrease in infarct size, serum lactate dehydrogenase activity, cardiomyocytes apoptosis, caspase-3 expression and activity, and a strong improvement in heart contractile function, compared with MI rats. Meanwhile, NPY siRNA (small interfering RNA) inhibited the cell apoptosis in H2O2-treated H9c2 cells and hypoxia-treated NRVMs. NPY deletion increased miR-499 expression and decreased FoxO4 expression in MI in vivo and in vitro. Moreover, NPY type 1 receptor (NPY1R) antagonist BIBO3304 can reverse miR-499 decrease and FoxO4 increase in H2O2-induced cardiomyocytes. NPY siRNA inhibited cell apoptosis in H2O2-treated H9c2 cells which were reversed by miR-499 inhibitor. Additionally, FoxO4 was validated as the direct target of miR-499. Moreover, BIBO3304 and FoxO4 siRNA significantly increased the cell activity, inhibited the cell apoptosis, and decreased caspase-3 expression and activity in H2O2-treated cardiomyocytes which NPY presented the opposite effect. Collectively, deletion of NPY reduced myocardial ischemia, improved cardiac function, and inhibited cardiomyocytes apoptosis by NPY1R-miR-499- FoxO4 axis, which provides a new treatment for MI.